Evaluation of the performance of turbot (Psetta maxima L.) in RAS with and without an upflow sludge blanket reactor - Sardinha, Manuel (2009)
Dissertação de mest., Aquacultura e Pescas, Faculdade de Ciências do Mar e do Ambiente, Universidade do Algarve, 2009 Aquaculture is the food production sector with higher development in the past years. This evolution must be based on economical and environmental sustainability. This work was part of an European project with the aim to understand the growth retardation in turbot cultured in RAS. For this, two different RAS were used, with (N=3) and without (N=3) an USB denitrifying reactor. This experiment, showed better growth rates, feed conversion, lower energy requirement for maintenance and higher retentions for fish reared under the denitrification reactor. It also showed, that this type of reactor reduces water exchange and nitrogen concentration in the water discharge, pointing to a environmentally sustainable development of the aquaculture sector, without affecting its competitiveness.